"ROLE OF EDUCATION IN THE DEVELOPMENT OF ENTREPRENEURIAL INTENTION," (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Entrepreneurship solves unemployment among  youth in India. It starts with the development of  (EI) in students. According to TPB, Intention  is the outcome of Attitude, S. N, and PBC,  the same holds for entrepreneurship intention.  Education influences students’ Attitude, S. N,  and he/she is receiving, so in this study, we  attempt to establish the relationship between  the antecedents of TPB and education. We conduct a study on the Indian students  belonging to graduation and post-graduation  of different specializations. In this study, a  “Five-point Likert scale” was employed and  239 samples collected from students were  used. We applied a path analysis algorithm  and bootstrapping procedure to establish the  relationship between the constructs and to check  the proposed hypotheses respectively in Smart  PLS 3.0. Education has a significant positive relationship  with the three antecedents of TPB. Apart from  this, attitude towards entrepreneurship and PBC  show a significant relationship with the (E. I) of  students, which supports the TPB. S. N does not show a positive significant relationship with the  (E. I) of students, which contradicts the research  conducted in past across the world. Study depicts the relationship of education  with factors formulating the “Entrepreneurial  Intention” (EI) that is new, as previous studies  conducted depict the relationship of education  directly with the (E. I) of students. Hence, the  study adds to the use of the “Theory of Planned  Behavior” in (E. I) development. The universities  and colleges can use this study to motivate  their students towards entrepreneurship by  providing the environment in an educational  institute and by teaching entrepreneurship to  all specializations.
Keywords: “Entrepreneurship”; Entrepreneurial Intention (E. I); “Subjective Norms (S. N); “Perceived Behavior Control (PBC); Theory of Planned Behavior (TPB)”; Attitude Towards Entrepreneurship (A. E)